The long revolution : creating a United States after 1776 - Perl-Rosenthal, Nathan, 1982- (Basic Books, 2026)
For America's 250th birthday, a provocative argument that a "Long Revolution" formed the violently beating heart of American politics for decades after 1776. In the century after Independence, many Americans believed that their Revolution was still in progress. Far from a unifying national myth, the Revolution was for generations of Americans a source of radically conflicting political ideas. Nowhere was this clearer than on the Fourth of July, when Americans gathered for speeches that, as one orator put it in 1834, aimed to "examine the present, and to look forward to the future." In The Long Revolution, historian Nathan Perl-Rosenthal mines thousands of Independence Day orations to offer a stirring and revelatory new history of this long American Revolution. In the words of local notables and national celebrities, men and women, white and Black, he identifies the contrasting visions, intense anxieties, and radical power evoked by the Revolution deep into the nineteenth century. This is a history of the American founding for today's fragmented and anxious political moment, helping us find a usable past to guide us toward our own uncertain future.